PENGEMBANGAN BUKU SMART GEOMETRY BOOK UNTUK PENGENALAN GEOMETRI ANAK USIA 5-6 TAHUN - YENI TRISTI ANTI; ARWENDIS WIJAYANTI; DITA PRIMASHANTI KOESMADI (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This development research aims to produce a Smart Geometry Book for the introduction of geometric shapes in children aged 5-6 years in TK Ngrambe sub-district. Smart Geometry Book is used to increase children's recognition of geometric shapes such as: Square, Triangle, Circle, Rectangle, Trapezoid and rhombus. This research uses research and development R&D (Research & Development) methods. Research and development in the world of education focuses on the development of designs and designs, whether in the form of design models, or teaching materials to be developed. This research method has stages of procedures carried out in the development of learning books, namely Analyze (analysis), Design (design), Develop (development), Implementation (implementation), and Evaluation (evaluation). Based on the results of the validation of effectiveness, efficiency, and attractiveness, it can be seen that the validation of media experts and material experts as well as the results of group and field trials conducted by 12 children, field trials conducted by 15 children, with the effectiveness aspect obtained an assessment result of 92 ,77%, the efficiency aspect gets an assessment result of 95%, and the attractiveness aspect gets an assessment result of 92.77%.